ANALISIS HUKUM MENGENAI PERJANJIAN YANG MEMUAT KLAUSULA TIDAK ADIL - , Zulfina Susanti ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study analyzes the law of the agreement containing the unfair clause. This study aims to determine what circumstances shall be concluded as containing unfair clause, and